Parametric finite element modeling and tooth contact analysis of spur and helical gears including profile and lead modifications. Issue 8 (6th November 2017) - Wang, Yanzhong; Liu, Yang; Tang, Wen; Liu, Peng
Abstract : Purpose: The finite element method has been increasingly applied in stress, thermal and dynamic analysis of gear transmissions. Preparing the models with different design and modification parameters for the finite element analysis is a time-consuming and highly skilled burden. Design/methodology/approach: To simplify the preprocessing work of the analysis, a parametric finite element modeling method for spur and helical gears including profile and lead modification is developed. The information about the nodes and elements is obtained and exported into the finite element software to generate the finite element model of the gear automatically. Findings: By using the three-dimensional finite element tooth contact analysis method, the effects of tooth modifications on the transmission error and contact stress of spur and helical gears are presented. Originality/value: The results demonstrate that the proposed method is useful for verifying the modification parameters of spur and helical gears in the case of deformations and misalignments.